Carbon balance implications of land use change from pasture to managed eucalyptus forest in Hawaii. Issue 3 (3rd July 2016) - Crow, Susan E.; Reeves, Mataia; Turn, Scott; Taniguchi, Shintaro; Schubert, Olivia S.; Koch, Nicholas
ABSTRACT: Mitigation of climate change via increased plant productivity and soil carbon (C) sequestration during land use change can be a powerful driver of the net greenhouse gas emissions of a sustainable production system. Yet the net climate change mitigation of managed forests is affected by both tradeoffs between C sequestration and non-renewable C emissions and assessment methodology. As a case study, we measured ecosystem stocks to determine the potential C implications of converting pasture to managed eucalyptus forest and compared them with the eucalyptus production system's non-renewable C emissions. The forest border was chosen as the system boundary and operations spanned from forest establishment activities to harvested wood placed at the forest perimeter. Eucalyptus biomass C was 57.2 ± 4.2 Mg C ha − 1 and soil C stock (to ∼1 m depth) was approximately an order of magnitude greater. By the prevalent method for bulk density-based determination of C stock, conversion of pasture to eucalyptus forest significantly increased soil C stock by 17.5 ± 8.0%. However, no significant change was detected by the equivalent soil mass method, a less prevalent but more accurate approach to detecting differences in soil C stock due to land use or management changes. A 7-year eucalyptus production cycle generated 1.0 Mg C ha − 1 in non-renewable emissions, which was far exceeded by the tree biomass C. Thus, even without significant soil C sequestration, this system provided a substantial climate change mitigation service by offsetting non-renewable energy use and C emissions associated with wood production, and providing opportunities for biofuel and bioenergy products to displace fossil fuel products.